HUBUNGAN PEMBAGIAN KERJA DAN WEWENANG KERJA TERHADAP PRESTASI KERJA PADA BRI KOTA KENDARI - Indrianti, Teti (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to determine the relationship between division of labour and work authority on work performance at BRI Kendari City, data collection was carried out using a questionnaire. Data obtained from 23 people. Data analysis using multiple linear regression. The results of the analysis show that the division of labour and work authority have a significant effect on work performance at BRI Kota Kendari, because the hypothesis proposed earlier is accepted. This can be seen from the sig t value of 0.000, when compared to the significant level of 0.05, the sig t value (0.000) < ? = 0.5 or 55 This can be interpreted that the research hypothesis (H 0) proposed is proven to be acceptable that there is a significant influence between the Work Division and Work Authority variables on work performance at BRI Kendari City or in other words if it is rejected or H1 is accepted, so that a decision can be made to reject H0 and H1 is accepted.